Peran Kebijakan Fiskal Hijau dalam Mendorong Keberlanjutan Ekonomi Hijau - Ayu Padila (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2026)
Green fiscal policies are important sustainable public instruments for the public sector in addressing climate change. Given that the global climate crisis generates significant economic and fiscal costs, green transformation requires public revenue and expenditure policies designed in accordance with the principles of a sustainable economy oriented toward green transformation. Fiscal policies focused on the green economy not only promote the transition from conventional economic systems to a green economy, but also have the capacity to steer private sector investment and savings toward more sustainable directions. This study aims to emphasize the importance of green fiscal policies in achieving the sustainability of a green economy by employing a literature review method. The findings indicate that green economic transformation cannot occur spontaneously through private sector actions alone; therefore, the active role of fiscal policy instruments is necessary to provide direction and incentives. Accordingly, green fiscal policies play a strategic role in driving sustainable fiscal and economic transformation and in strengthening the relationship between green economic transformation and green fiscal policies.